Osteodifferentiation of Human Preadipocytes Induced by Strontium Released from Hydrogels - Valeria Nardone; Sergio Fabbri; Francesca Marini; Roberto Zonefrati; Gianna Galli; Annamaria Carossino; Annalisa Tanini; Maria Luisa Brandi (International Journal of Biomaterials)
In recent years, there has been an increasing interest in interactive application principles of biology and engineering for the development of valid biological systems for tissue regeneration, such as for the treatment of bone fractures or skeletal defects. The application of stem cells together with biomaterials releasing bioactive factors promotes the formation of bone tissue by inducing proliferation and/or cell differentiation. In this study, we used a clonal cell line from human adipose tissue-derived mesenchymal stem cells (hADSCs or preadipocytes), named PA2-E12, to evaluate the effects of strontium (Sr2+) released in the culture medium from an amidated carboxymethylcellulose (CMCA) hydrogel enriched with different Sr2+ concentrations on osteodifferentiation. The osteoinductive effect was evaluated through both the expression of alkaline phophatase (ALP) activity and the hydroxyapatite (HA) production during 42 days of induction. Present data have shown that Sr2+ released from CMCA promotes the osteodifferentiation induced by an osteogenic medium as shown by the increase of ALP activity at 7 and 14 days and of HA production at 14 days. In conclusion, the use of biomaterials able to release in situ osteoinductive agents, like Sr2+, could represent a new strategy for future applications in bone tissue engineering.